نظام تعليم اللغة العربية لتنمية مهارة الكتابة في دار العربي بمعهد السنية كنشونج جمبر للسنة الدراسية 2017/2018م - Nafsah, Nor Holis Bin (Al-Fusha : Arabic Language Education Journal, 2018)
The education system is the real basis for achieving the desired goals in the learning and teaching process, which determines the success of the failure of any educational project. It consists of four important elements, inputs and processes, then outputs or ????inal results, and a comparison of the results obtained with the criteria or bjectives set in the feedback. The problems of this research are: How the system of teaching Arabic language to develop writing skill in Darul Arobi in the Assunniyyah Islamic Boarding School of Kencong Jember for the academic year 20172018/. In this research, the researcher chose the descriptive approach with qualitative input. The sample of this research is the director of the Assunniyyah Islamic Boarding, the director and supervisor of Dar Al Arabi, and students who specialize in learning Arabic in Dar Al-Arabi in three stages.